Making Insurance Markets Work for Farmers in India - Mahul, Olivier; Verma, Niraj (World Bank, Washington, DC, 2012)
India's crop insurance program is the world's largest with 25 million farmers insured. Yet 85 million farmer households are not covered. Issues in design, particularly related to delays in claims settlements, explain the low coverage. To address these problems, the World Bank provided actuarial inputs, engaged in policy dialogue, and facilitated the launch of an innovative crop insurance program that will improve equity, risk mitigation, and claims settlement for farmers; provide tools for budget management and agricultural policy for government; and open up the market for public- and private-sector insurers and reinsurers. Initially, the program will be available to an estimated 8 to 10 million farmers, of whom 3 million are expected to participate in the first year with a total sum insured in excess of $1 billion. Over time, this project could be scaled up to be available to India's 110 million farmers. This smart lesson describes lessons learned in developing and implementing the crop insurance program.